Effect of triceps surae and quadriceps muscle fatigue on the mechanics of landing in stepping down in ongoing gait - Barbieri, F. A. [UNESP]; Gobbi, L. T. B. [UNESP]; Lee, Y. J. [UNESP]; Pijnappels, M. [UNESP]; van Dieen, J. H. (Taylor & Francis Ltd, 2014)
The aim of this study was to evaluate the effects of muscle fatigue of triceps surae and quadriceps muscles in stepping down in ongoing gait. We expected that the subjects would compensate for muscle fatigue to prevent potential loss of balance in stepping down. A total of 10 young participants walked over a walkway at a self-selected velocity to step down a height difference of 10-cm halfway. Five trials were performed before and after a muscle fatigue protocol. Participants performed two fatigue protocols: one for ankle muscle fatigue and another for knee muscle fatigue. Kinematics of and ground reaction forces on the leading leg were recorded. Fatigue did not cause a change in the frequency of heel or toe landing. Our results indicate that in stepping down fatigue effects are compensated by redistributing work to unfatigued muscle groups and by gait changes aimed at enhancing balance control, which was however only partially successful.Practitioner Summary: Problems with transitions between levels in gait are common causes of falls. Fatigue can affect the ability to dissipate energy gained during the step down. The main finding was that young adults recruited unfatigued muscle groups and adjusted their gait pattern to compensate the fatigue effects during landing.
Keywords: muscle fatigue; stepping down; gait; balance control